The effect of prenatal balanced energy and protein supplementation on gestational weight gain: An individual participant data meta-analysis in low- and middle-income countries - Wang, Dongqing; Partap, Uttara; Liu, Enju; Costa, Janaína Calu; Cliffer, Ilana R.; Wang, Molin; Nookala, Sudeer Kumar; Subramoney, Vishak; Briggs, Brittany; Ahmed, Imran; Argaw, Alemayehu; Ariff, Shabina; et al. (2025)
Background Understanding the effects of balanced energy and protein (BEP) supplements on gestational weight gain (GWG) and how the effects differ depending on maternal characteristics and the nutritional composition of the supplements will inform the implementation of prenatal BEP interventions.